Analisis Antrian Dan Solusi Optimalisasi Pada Pelayanan Miniso di Suzuya Mall Rantauprapat - Sofyan, Hadron; Maulana, Rezky; Wardana, Priya; Ritonga, Irmayanti (Universitas Labuhanbatu, 2025)
This study aims to analyze the queuing system at Miniso's services in Suzuya Mall Rantauprapat, focusing on queue patterns, service efficiency, and optimization solutions. Using the M/M/1 queue theory model, the study reveals an imbalance in service capacity, especially during peak hours, leading to increased customer waiting times and decreased satisfaction levels. Proposed solutions include adding more cashiers, implementing an electronic queue system, and scheduling work shifts based on data. These strategies are expected to reduce waiting times, enhance operational efficiency, and provide a better customer experience.